WANITA KARIR PERSPEKTIF HUKUM ISLAM SERTA IMPLIKASINYA (STUDI KASUS DI KECAMATAN MUTIARA) - Aldin, Alfattiah; Windari, Silmi (Jurnal Tahqiqa : Jurnal Pemikiran Hukum Islam, 2025)
This research aims to determine the perspective of Islamic law regarding career women. To find out the position of career women in Islamic law and the impact of career women who work outside the home in Mutiara District. The research method used is qualitative descriptive research. The results of this research show that (1) Career women from an Islamic perspective are viewed from their position as creatures, that Islam gives women a proper position and degree as well as the same status as men in their capacity as servants of God. Islam does not prohibit women or wives from working, as long as they do not neglect their main obligations. Islam recommends that women who work outside the home obtain permission from their husbands, because the husband's approval for career women is the main requirement. (2) The impact of women working outside the home can be seen from two sides, namely from the negative side and the positive side. The negative impact is reduced social interaction, reduced time with family. The positive impacts include, by working, she will gain more knowledge and relationships, provide knowledge to the community and from an economic perspective it will greatly lighten her husband's burden.